PRODUCTION OF CONIDIA BY ENTOMOPATHOGENIC FUNGI AND THEIR PATHOGENICITY AGAINST COPTOTERMES SP. - Zulfiana, Deni; Zulfitri, Apriwi; Lestari, Anis Sri; Krishanti, Ni Putu Ratna Ayu; Meisyara, Dita (Biosaintifika: Journal of Biology & Biology Education, 2020)
Entomopathogenic fungi have the potential to infect most arthropods including termites which are economically important major insects pest of wood, wood products and building structures. However, the application of this fungus in the field has not shown satisfactory results yet, one of which is constrained in mass production of conidia. The purpose of this study was to evaluate 16 types of biodegradable products and waste as substrates for mass production of conidia using solid state fermentation method and two types of inoculum namely solid and liquid inoculum. Toxicity tests were carried out on subterranean termites (Coptotermes sp.) based on JIS K 1571, 2010. The parameters observed were the number and dry weight of the conidia produced, conidial viability, nutrient content of the substrate, and percentage of termite mortality. The results showed that rice, sorghum and corn were the best media for the growth of entomopathogenic fungi based on the number of conidia and dry weight of the conidia produced. Metarhizium sp. T4.B23 produced the highest number of conidia, 1.12 x 1011 conidia/100 g substrate and yielded 180.9 ± 0.623 g dry conidia/kg of rice; followed by Metarhizium sp. B2.2 grown on sorghum that resulted in 1.11 x 1010 conidia/100 g substrates and 8 ± 0.570 g /kg sorghum; and B. bassiana produced 8.3 x 109 conidia/100 g substrate and 31.24 ± 0.407 gr/ kg sorghum. Metarhizium sp. B2.2 showed the highest toxicity to termites with 100% mortality was observed within the second day of testing. Therefore the conidia of Metahizium sp. B2.2 is potential to be developed as a biopesticide using rice or sorghum substrate as a carrier.